Analisis Ekonomi Manajerial dan Strategi PT Perusahaan Gas Negara TBK (PGN) - Ega Juangga; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by PT Perusahaan Gas Negara Tbk (PGN) and formulate cost management optimization strategies to enhance the company’s financial performance. As Indonesia’s national gas subholding, PGN plays a vital role in national energy security through its extensive gas infrastructure and operational efficiency programs. The method used in this study is a qualitative-descriptive approach based on secondary data from financial reports, annual reports, official publications, and academic sources. The findings reveal that PGN's strong infrastructure and efficiency measures are key strengths, though the company faces significant threats from energy price volatility, regulatory changes, and internal control limitations. Strategies formulated include supply diversification, internal monitoring reinforcement, gas price reform, and collaboration with government stakeholders. This research contributes to the formulation of sustainable business strategies through SWOT-based analysis, supporting national energy resilience.